Analysis of the Viscosity Ratio of Two-Phase Flow in a Porous Media by Numerical Modeling (LACCEI, 2024)
The objective of this research is to analyze the behavior of the two-phase flow in the homogeneous porous media during the waterflooding process and thus obtain a better description of the fluid flow. A mathematical model of the two-phase flow in a porous media was used as a starting point to subsequently build the numerical model. For the numerical model, the fully implicit method was used for the discretization in time and the finite volume method for the discretization in space. The algebraic equations representing the two-phase flow in a porous media were linearized using the Newton-Raphson method because they are nonlinear and strongly coupled. In order to know the influence of fluid viscosities, three simulation cases were run considering a viscosity ratio value less than 1 as the first scenario, a second case with a viscosity ratio value equal to 1 and a third case considering a viscosity ratio value greater than 1. The results of the numerical simulations show that the studied variable considerably influences the two-phase flow in the porous media during waterflooding.